Empirical Study on Distribution-Centric Marketing and Operational Challenges of FMCG in Rural Markets - S. Jothipriya; Dr. J. Josephine Daisy (IJRDO - Journal of Business Management, 2025)
FMCG are distributed using distribution structures that rely on daily work of distributor who are involved in controlling product movement, distribution coverage of retailers, logistics and promotion. Rural markets work with the dynamics of distance, low density of population, and low infrastructure levels since all factors impact the effectiveness of marketing based on distribution. This paper analyzes the marketing and operational issues experienced by FMCG distributors in rural areas of Salem District due to their experience since it dictates the success of products in penetrating the interior markets. The study collected primary data among 193 distributors were subjected to a structured interview schedule to gather personal interaction as this accurately reflects the realities in the field. The research design is empirical due to the relationship between the logistics, credit practice, timing of delivery, expectations of the retailers and marketing support at the company level which are seen to be intertwined. The statistical tools of factor analysis, discriminant analysis and Conjoint analysis is used to determine the relative importance of important distribution features since distributors give the various characteristic attributes of delivery consistency. The findings indicate that the concerns distributors have are reliability and speed since rural retailers rely on the supply of products when needed. The operational problems come into picture when the distributors experience transportation delays, increasing cost, scarcity of manpower and lack of promotional backing.